Radiofrequency Energy in Hepatic Bed during Partial Cystectomy for Hydatid Liver Disease: Standing Out from the Usual Conservative Surgical Management. (21st July 2016) - Mantonakis, Eleftherios; Papalampros, Alexandros; Moris, Demetrios; Dimitrokallis, Nikolaos; Sakarellos, Panagiotis; Griniatsos, John; Felekouras, Evangelos
Abstract : Background . Surgical treatment of hydatid liver disease (HLD) is divided into conservative and radical procedures. While conservative techniques are easier and faster to perform, there is an emerging need to reduce their morbidity and recurrence rates. Our aim was to present and evaluate the efficiency and safety of the application of radiofrequency energy (TissueLink® and Aquamantys® systems) in hepatic bed during partial cystectomy. Materials and Methods . Eighteen consecutive patients with hydatid liver cysts were referred to our department between April 2006 and June 2014. Data about demographics, mortality, morbidity, and recurrence rate were obtained and analyzed retrospectively. Results . The mean follow-up was 38 months (range: 4–84 months). The postoperative course of most patients was uneventful. One case of recurrence was found in our series in a patient with 4 cysts in the right lobe, 3 years after initial treatment. He was reoperated on with the same method. Conclusions . Saline-linked RF energy seems to be an effective means to be employed in conservative surgical procedures of HLD, with satisfactory postoperative morbidity. Recurrence rates appear to be low, but further follow-up is needed in order to draw safer conclusions.